Regional Aβ-tau interactions promote onset and acceleration of Alzheimer’s disease tau spreading - Lee, Wha Jin; Brown, Jesse A.; Kim, Hye Ryun; La Joie, Renaud; Cho, Hanna; Lyoo, Chul Hyoung; Rabinovici, Gil D.; Seong, Joon-Kyung; Seeley, William W. (Neuron (Cambridge, Mass.), 2022)
Amyloid-beta and tau are key molecules in the pathogenesis of Alzheimer’s disease, but it remains unclear how these proteins interact to promote disease. Here, by combining cross-sectional and longitudinal molecular imaging and network connectivity analyses in living humans, we identified two amyloid-beta/tau interactions associated with the onset and propagation of tau spreading. First, we show that the lateral entorhinal cortex, an early site of tau neurofibrillary tangle formation, is subject to remote, connectivity-mediated amyloid-beta/tau interactions linked to initial tau spreading. Second, we identify the inferior temporal gyrus as the region featuring the greatest local amyloid-beta/tau interactions and a connectivity profile well suited to accelerate tau propagation. Taken together, our data address long-standing questions regarding the topographical dissimilarity between early amyloid-beta and tau deposition. [Display omitted] •Network flow-based model identifies tau propagation hubs in inferior temporal gyri•Remote Aβ-tau interactions in entorhinal cortex may trigger initial tau spreading•Local Aβ-tau interactions in inferior temporal gyrus may promote tau propagation•Connectivity-based model addresses the spatial incongruity between early Aβ and tau Lee et al. show that the natural history of AD traverses a critical period that begins once Aβ emerges within entorhinal cortex (EC)-connected regions, continues as tau spreads from the EC into connected mesial temporal and limbic regions, and may end once Aβ and tau interact within the inferior temporal gyrus propagation hubs, whose connections are well suited to facilitate widespread neocortical tau propagation.